2020
DOI: 10.1166/sam.2020.3640
|View full text |Cite
|
Sign up to set email alerts
|

Different Alignment Between Skeletal and Smooth Muscle Cells on Reduced Graphene Oxide-Patterned Arrays

Abstract: Cells respond directly to the chemical and topographical cues of the engineered substrate. To date, recent extensive studies have been witnessed on the wide development of biomimetic substrates that can regulate the cellular behaviors by establishing the specific cues of the substrate. It is well known that the topographical features with nanoscale and microscale strongly modulate the behaviors of cells, including adhesion, migration, proliferation, and differentiation. Herein, we present a simple and robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…GO represents an effective reinforcing agent due to the strengthening effect on the soft collagen scaffold [116] and also due to the biological activity exerted through multiple functional groups, which increases the similarity of the morphology of the nanocomposite to that of natural bone and guides ions through the network to achieve mineralization. A recent study demonstrated that GO represents an important component in a scaffold designed for tissue engineering due to the ability to control cellular behavior [117].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…GO represents an effective reinforcing agent due to the strengthening effect on the soft collagen scaffold [116] and also due to the biological activity exerted through multiple functional groups, which increases the similarity of the morphology of the nanocomposite to that of natural bone and guides ions through the network to achieve mineralization. A recent study demonstrated that GO represents an important component in a scaffold designed for tissue engineering due to the ability to control cellular behavior [117].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Of these cell types, C2C12 cells demonstrated preferential morphological alignment along the rGO patterned arrays, suggesting that nanoscale rGO arrays may be used to control skeletal muscle cell morphology and differentiation. [ 114 ] Similarly, graphene nanoribbon (GNR) patterning has been employed to align myoblasts on low modulus (≈36.2 kPa) polydimethylsiloxane (PDMS) with mechanical properties similar to native skeletal muscle. [ 115 ] GNR incorporation facilitated in vitro physiological monitoring by providing a direct interface between patterned cells and impedance and temperature sensors integrated into the PDMS, yielding a muscle‐on‐a‐chip for testing novel nanomaterials.…”
Section: Properties Of Graphene Family Nanomaterialsmentioning
confidence: 99%
“…In particular, graphene and its derivatives can be utilized as tissue engineering scaffold materials because they have known to enhance cellular behaviors such as adhesion, proliferation, and migration [ 26 28 ]. Owing to the hydrophilic and cell-adhesive nature, graphene and its derivatives are utilized as the micro-patterned scaffold to enable contact guidance of cells [ 29 32 ]. Furthermore, previous researches indicated that graphene derivatives induce cells to differentiate to specific lineages such as adipogenesis, chondrogenesis, myogenesis, neuritogenesis, and osteogenesis [ 33 40 ].…”
Section: Introductionmentioning
confidence: 99%